Association between Serum Total Cholesterol Levels and Unfavourable Outcome in Patients with Spontaneous Intracerebral Hemorrhage - Akram, Samra; Sohail, Sharjeel; Ahmed, Nauman; Saleem, Mohiuddin; Asad, Hira (Indus Journal of Bioscience Research, 2025)
Background: To determine the association between low serum total cholesterol levels and unfavorable outcomes in patients with spontaneous ICH. Methods: This prospective cohort study was conducted in the Department of Neurosurgery, Shaikh Zayed Hospital, Lahore, from February 2025 to June 2025. A total of 200 patients aged 30–90 years presenting within 72 hours of ICH onset were enrolled and categorized into two groups based on fasting serum TC levels: exposed group (